TRIM6 Reduces Ferroptosis and Chemosensitivity by Targeting SLC1A5 in Lung Cancer. (9th January 2023) - Zhang, Ying; Dong, Ping; Liu, Nian; Yang, Jun-Yuan; Wang, Hui-Min; Geng, Qing
Abstract : Objective . Ferroptosis, a newly identified form of cell death, plays critical roles in the development and chemoresistance of lung cancer. Tripartite motif 6 (TRIM6) acts as an E3-ubiquitin ligase and can promote the progression of human colorectal cancer. The present study is aimed at investigating its role and potential mechanisms in lung cancer. Methods . Lentiviral vectors were used to overexpress or knock down TRIM6 in human lung cancer cells. Cell survival, colony formation, lipid peroxidation, intracellular iron levels, and other ferroptotic markers were examined. The role of TRIM6 on ferroptosis and chemosensitivity was further tested in mouse tumor xenograft models. Results . TRIM6 was highly expressed in human lung cancer tissues and cells, and its expression in the lung cancer cells was further increased by ferroptotic stimulation. TRIM6 overexpression inhibited, while TRIM6 silence promoted erastin- and RSL3-induced glutaminolysis and ferroptosis in the lung cancer cells. Mechanistically, TRIM6 directly interacted with solute carrier family 1 member 5 to promote its ubiquitination and degradation, thereby inhibiting glutamine import, glutaminolysis, lipid peroxidation, and ferroptotic cell death. Moreover, we observed that TRIM6 overexpression reduced the chemotherapeutic effects of cisplatin and paclitaxel. In contrast, TRIM6 silence sensitized human lung cancer cells to cisplatin and paclitaxel in vivo and in vitro. Conclusion . Our findings for the first time define TRIM6 as a negative regulator of ferroptosis in the lung cancer cells, and TRIM6 overexpression enhances the resistance of human lung cancer cells to chemotherapeutic drugs. Overall, targeting TRIM6 may help to establish novel strategies to treat lung cancer.